Exploring the Buddha's Journeys and Students' Perception of Buddhist Adventure-Based Digital Games to Enhance English Language Skills - Anthonius, Ferdy; Wong, Mettadewi; Aryusmar, Aryusmar; Chong, Henry (Bina Nusantara University, 2025)
This research aims to explore the Buddha's journeys, the concept of Buddhist adventure-based digital games, and students' perception of Buddhist adventure-based digital games to enhance English language skills. This research employs descriptive research with a quantitative method. Questionnaires were distributed to 98 non-English students majoring in Buddhism who have experienced English language learning using Buddhist adventure-based digital games at Nalanda Institute in Jakarta after the lecturer integrated the game as a teaching tool, with the research conducted from March to July 2024. The findings indicate that 1) 95.90% of students have a good knowledge of the concept of digital games for learning English; 2) 100% of students have a good understanding of the Buddha Adventure; 3) 99.00% of students enjoyed learning English using digital games; 4) 95.90% of students are interested in incorporating these games into their English studies; 5) 96.90% of students have a good comprehension of learning English through Buddhist adventure-based digital games as a learning medium; 6) 98.00% of students support the effectiveness of this game to enhance their language skills, including listening, speaking, reading, and writing. Therefore, this study concludes that the perceptions of non-English students majoring in Buddhism towards Buddhist adventure-based digital games as a medium for learning English are highly significant. The results of this research imply that Nalanda Institute should integrate these findings into its learning policies.